Violence, peace and legal perspective (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This article puts forward a contemporary reflection about violence based on a finalist legal assessment of peace. For that purpose, it both distinguishes and relates these two concepts, particularly regarding their politically motivated expressions, as well as it highlights the functionality of law to achieve negative peace and the ensuing morality of positive peace. In doing so, it considers the works written on this subject by influential contemporary authors as a reference point, after which it projects a legal perspective on violence through the analysis of three dimensions of this phenomenon that rely on categories both of legal theory and legal philosophy. This paper concludes that the final motivations that bring about conflict among States, groups and individuals admit similarities among themselves when they are pushed to the maximum level of incivility and irrationality. Likewise, it states that the distinction between law and morality is used improperly by those who use violence as a method for political action because they pretend to justify their actions therein as a way to ignore or evade their being as subjects ruled by the law.
Keywords: political violence; social peace; purposes of the law; war; Philosophy of Law